Increasing Students’ Speaking Ability Through Different Context of Materials Strategy for the Sixth Graders of SDN 01 Rensing Bat - Karomi Safari, M. Ubaidillah (MODELING: Jurnal Program Studi PGMI, 2022)
This study is aimed to investigate students’ ability in speaking during conversation and to what extent students’ ability in carrying out conversation through different context of material strategy given by teacher. The problems were (1) How were students’ speaking ability during conversation through different context of materials given by teacher?. (2) To what extent students’ speaking ability during conversation through different context of materials?. This study was descriptive qualitative study. Population was the sixth graders of SDN 01 Rensing Bat which consist of 30 students. Instrument used of data was speaking test. The data analyzed by analytic scoring in Browns’ theories. Results of study showed that students were able to speak during conversation with whole aspects of speaking skill. They proved by data of achievement ranges from C (fair) to A (good) with 30 students achieved (99.9%). While, data showed number of students achieved rating level of D (poor) and E (very poor) was none students (0.0%). In addition, Mean Score achieved (17.6) while Standard Deviation was (2.27). by this data clearly showed that the sixth graders of SDN 01 Rensing Bat were fair level in speaking skill.